Estudo térmico de um sistema solar de aquecimento de água residencial para duas configurações de superfície absorvedora - Abreu, Rivaldo Ferreira de (2009)
It presents a solar collector to be used in a system for heating water for bathing, whose main characteristics are its low cost and easy manufacturing and assembly. The absorbing surface of the collector is formed by an aluminum plate with eight flaps where they lodge PVC pipes. The catchment area of solar radiation corresponds to 1.3 meters. The collector box was made of wood, is covered by transparent glass and thermal insulation of tire chips and expanded polystyrene (EPS). Absorber tubes were connected in parallel through the use of PVC fittings and fixed to the plate by the use of metal poles and rivets. The entire absorber received paint flat black for better absorption of sunlight. The system worked on a thermosiphon assembly and absorber of the collector has been tested in two configurations: with the tubes facing up, directly exposed to the impact of sunlight and facing down, exchanging heat with the plate by conduction. It was determined the most efficient configuration for the correct purpose. The solar collector was connected to a thermal reservoir, also alternative, low-cost forming the system of solar water heating. We evaluated thermal parameters that proved the viability of the heating system studied